Strategic Plan for Strengthening of Internal Audit in Government of Bihar - World Bank (Washington, DC, 2013)
The Government of Bihar (GOB) has adopted various reform measures to modernize fiscal and financial management such as passing of the Fiscal Responsibility and Budget Management Act, adoption of Government of India's general financial rules and decentralization of financial powers to respective departments with a view to increasing the pace of expenditure and implementation of plan schemes. However, for decentralization to be effective the supporting public financial management systems need to be also modernized. Accordingly, the Government had entrusted a project 'modernization of budget and financial rules and procedures' to Centre for Good Governance (CGG), Hyderabad. The project requires CGG to comprehensively revise the treasury code, financial rules and budget manual, and to provide a roadmap to modernize and strengthen internal audit function in the government. CGG has firstly studied the existing organization structure of the internal audit function in GOB, the skills and capacity of the internal audit staff, the working conditions in the main office and divisional offices, the perception of others about internal audit and so on. They have visited the main office in Patna and the divisional office in Gaya. After identifying the strengths and weaknesses of the system, a road map has been prepared for strengthening the internal audit in the government.